Rehabilitacija oseb s kompleksnim regionalnim bolečinskim sindromom tip 1 - Kos, Nataša (Rehabilitacija (Ljubljana), 2010)
Complex regional pain syndrome (CPRS) is a neuropathic pain condition characterized by disturbances of sensory, motor and autonomic function that may be associated with trophic changes. The treatment consists of concurrent utilisation of pharmacotherapeutic, psychotherapeutic and physiotherapeutic modalities to restore function and health. Many treatments have been developed to manage this condition. Existing CRPS guidelines for specific physiotherapy treatment should be updated to ensure that recommendations are clinically effective, relevant and based on the best available evidence.
Keywords: bolečina; bolečinski sindrom; fizikalna terapija; nevropatska bolečina; rehabilitacija; vocational rehabilitation